Immunomodulation as Therapy for Fungal Infection: Are We Closer? - Sam, Qi Hui; Yew, Wen Shan; Seneviratne, Chaminda J.; Chang, Matthew Wook; Chai, Louis Yi Ann (Frontiers in Microbiology, 2018)
Invasive fungal disease (IFD) causes significant morbidity in immunocompromised patients due to their weakened immune system. Immunomodulatory therapy, in synergy with existing antifungal therapy, is an attractive option to enhance their immune system and aid clearance of these opportunistic pathogens. From a scientific and clinical perspective, we explore the immunotherapeutic options to augment standard antifungal drugs for patients with an IFD. We discuss the range of immunomodulatory therapies being considered in IFD – from cytokines, including G-CSF, GM-CSF, M-CSF, IFN-γ, and cytokine agonists, to cellular therapies, consisting of granulocyte transfusion, adoptive T-cell, CAR T-cell, natural killer cell therapies, and monoclonal antibodies. Adjunct pharmaceutical agents which augment the immunity are also being considered. Lastly, we explore the likelihood of the use of probiotics and manipulation of the microbiome/mycobiome to enhance IFD treatment outcomes.